2009
DOI: 10.1016/j.micres.2006.11.011
|View full text |Cite
|
Sign up to set email alerts
|

The incomplete substitution of lipopolysaccharide with O-chain prevents the establishment of effective symbiosis between Mesorhizobium loti NZP2213.1 and Lotus corniculatus

Abstract: Mesorhizobium loti NZP2213.1 mutant obtained after random Tn5 mutagenesis of M. loti NZP2213 was inefficient in nitrogen fixation on Lotus corniculatus. The transposon insertion was located within an ORF with a sequence similarity to a putative glycosyl transferase from Caulobacter crescentus. The results of sodium dodecyl sulfate-polyacrylamide gel electrophoresis indicated that the mutant produced LPS of the same O-chain length but only half of the entire smooth LPS, compared to that of the parental strain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 27 publications
1
19
0
1
Order By: Relevance
“…The rhizobial O-chain biosynthetic machinery seems to be particularly stringent in this regard. Among published rhizobial structures, neutral OPS that have some degree of hydrophobicity appear to be favored, and residues imparting net negative charge are either absent (6,16) or when present are blocked by esterification (as in R. etli CE3) or neutralized with a positive substituent (N-acetimidoyl group, shown here for R. leguminosarum) to yield the zwitterion. At normal physiological pH, at or around neutrality, it would be expected that the RL3841 OPS has no net charge, and this is the form believed to be expressed while the bacteria adhere and colonize the plant surface.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The rhizobial O-chain biosynthetic machinery seems to be particularly stringent in this regard. Among published rhizobial structures, neutral OPS that have some degree of hydrophobicity appear to be favored, and residues imparting net negative charge are either absent (6,16) or when present are blocked by esterification (as in R. etli CE3) or neutralized with a positive substituent (N-acetimidoyl group, shown here for R. leguminosarum) to yield the zwitterion. At normal physiological pH, at or around neutrality, it would be expected that the RL3841 OPS has no net charge, and this is the form believed to be expressed while the bacteria adhere and colonize the plant surface.…”
Section: Discussionmentioning
confidence: 88%
“…The lipopolysaccharides (LPS) 2 are major structural and antigenic components of the rhizobial outer membrane, and are suitably located to interact with the plant membrane components and soluble plant products existing in the peribac-teroid space (2-5, 11, 12). Numerous studies with rhizobial LPS mutants containing structurally defined defects have indicated that a structurally intact LPS, expressed at normal levels, is essential for normal root nodule development and active nitrogen fixation (Ndv ϩ , Fix ϩ phenotype) (2,5,6,(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…However, other rhizobial factors including β-glycans, exopolysaccharides (EPS) and lipopolysaccharides (LPS) are also known to play important roles at the earliest stages of the interaction by mediating root attachment, participating in infection thread formation and avoiding plant defence reactions in indeterminate nodules (Jones et al 2007). In determinate nodulating hosts, the role of these rhizobial surface molecules is still unclear, although the ability to form efficient nodules of M. loti mutants deficient in LPS and/or cyclic glycans but not EPS, was reduced (Hotter and Scott 1991;Lepek et al 2002;Turska-Szewczuk et al 2009). Thus, the common changes in the level of the phenolic compounds after inoculation with both M. loti strains detected here may be induced by plant recognition of these other rhizobial factors.…”
Section: Discussionmentioning
confidence: 99%
“…Równocześnie znacznie zmniejszył się stopień podstawienia oligosacharydu rdzeniowego tak zmodyfikowanym O-PS, co pociągnęło za sobą zmiany hydrofobowości komórek bakteryjnych. Konsekwencją tych zmian był nieprawidłowy rozwój nici infekcyjnych, przedwczesne starzenie się i degradacja symbiosomów w brodawkach indukowanych przez mutanta M. loti NZP2213.1 na komonicy zwyczajnej (Lotus corniculatus) [80,81].…”
Section: Rola Lipopolisacharydu W Procesie Symbiozyunclassified